Preparation method, product and application of copper oxide loaded iron cerate negative electrode material

The preparation of copper oxide-loaded iron cerate anode material is solved by chemical solution method, which solves the problem of insufficient conductivity of the negative electrode materials of existing lithium-ion batteries, improves electrochemical performance and cycle life, and enhances the application capabilities of the battery.

CN119400836APending Publication Date: 2025-02-07SHANGHAI NAT ENG RES CENT FORNANOTECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411573620.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

Existing lithium-ion battery negative electrode materials such as carbon materials have problems such as electrolyte consumption, low efficiency for the first time, and easy formation of lithium dendrites and short circuits during overcharging. The lithium ion diffusion coefficient is small, which limits the application range of the battery.

Method used

The copper oxide-laden iron cerate negative electrode material is prepared by chemical solution method, and the copper oxide loading improves the conductivity of iron cerate, thereby improving the electrochemical performance of the material.

Benefits of technology

It improves the conductivity and electrochemical properties of the material, enhances the power and energy density of lithium-ion batteries, extends the cycle life, and reduces the risk of battery overcharge.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
Patent Text Reader

Abstract

The invention provides a preparation method of a copper oxide-loaded ferric cerate negative electrode material and a product and application thereof, the copper oxide-loaded ferric cerate negative electrode material is prepared by a chemical solution method, ferric salt and cerium salt are added into an alcohol / aqueous solution for ultrasonic dispersion, a strong alkali solution is added for continuous ultrasonic treatment, stirring, filtering, washing and overnight drying under vacuum are performed to obtain ferric cerate; the preparation method comprises the following steps: dispersing ferric cerate in ethanol, adding organic copper salt, distilled water and ammonia water, carrying out ultrasonic water bath heating at room temperature, washing and vacuum-drying centrifugally separated precipitate to obtain powder, and carrying out heat treatment on the dried powder to obtain the copper oxide loaded ferric cerate negative electrode material. According to the prepared negative electrode material, under the condition of the current density of 500 mA / g, the first discharge specific capacity is 1770 mAh / g, the third discharge specific capacity is 889 mAh / g to the 50th discharge specific capacity is 825 mAh / g, and compared with the third discharge specific capacity, the capacity retention ratio is 92.8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a negative electrode material for a lithium battery, and in particular to a method for preparing a copper oxide-loaded iron ceria negative electrode material, a product and an application thereof, and a method for preparing a copper oxide-loaded iron ceria negative electrode material for a lithium ion battery. Background Art

[0002] With the development of society, lithium-ion batteries have attracted much attention. Lithium-ion batteries are currently the most ideal rechargeable batteries in the world. They not only have the advantages of high energy density, long cycle life, no memory effect and low pollution, but also have the advantages of high energy density, long cycle life, no memory effect and low pollution. With the advancement of technology, lithium-ion batteries will be widely used in electric vehicles, aerospace, biomedicine and other fields. Therefore, the research and development of power lithium-ion batteries and related materials is of great significance. For power lithium-ion batteries, the key is to improve power density and energy density, and the fundamental to improve power density and energy density is the improvement of electrode materials, especially negative electrode materials.

[0003] Since the early 1990s, Japanese scientists have developed layered carbon materials. Carbon materials are the earliest materials studied and applied to the commercialization of lithium-ion batteries. They are still one of the focuses of attention and research. However, carbon negative electrode materials have some defects: when the battery is formed, it reacts with the electrolyte to form an SEI film, resulting in electrolyte consumption and low initial coulombic efficiency; when the battery is overcharged, metallic lithium may precipitate on the surface of the carbon electrode to form lithium dendrites, causing a short circuit, resulting in temperature rise and battery explosion; in addition, the diffusion coefficient of lithium ions in carbon materials is small, resulting in the battery being unable to achieve large current charging and discharging, thereby limiting the application range of lithium-ion batteries.

[0004] Ferric ceria is a spinel-structured composite oxide that can also be used as a negative electrode material for lithium-ion batteries. It has a high Li+ storage capacity through conversion and alloying reactions. This material is considered to be a promising lithium-ion negative electrode material.

[0005] The present invention provides a method for preparing a copper oxide-loaded iron ceria anode material, wherein the copper oxide-loaded iron ceria is prepared by a chemical solution method, and the conductivity of the iron ceria is further improved by the loading of copper oxide, which is further beneficial to improving the electrochemical performance of the material. The preparation process is relatively simple and easy to operate. Summary of the invention

[0006] In order to overcome the disadvantage that the electrochemical performance of the existing ferric cerate is not high enough, the present invention aims to provide a method for preparing a copper oxide-loaded ferric cerate negative electrode material.

[0007] Another object of the present invention is to provide a copper oxide-loaded ferric ceria product obtained by the above method.

[0008] Another object of the present invention is to provide an application of the above product.

[0009] The object of the present invention is achieved by the following scheme: A method for preparing a copper oxide-loaded iron ceria anode material, which is prepared by a chemical solution method and comprises the following steps: (1) Add 100 mL of alcohol / water solution in a volume ratio of 1:1 into a flask, add iron salt and cerium salt into the alcohol / water solution, wherein the molar stoichiometric ratio of iron to cerium is 1:1, and ultrasonically disperse for 10 to 20 min. Then, add 20 mL of a 2 M strong base solution, and continue ultrasonic treatment for 10 to 20 min to obtain a mixture; (2) After stirring the mixture at 60-80°C for 5-8 h, the mixture was filtered and washed with 10 mL of alcohol, and dried overnight at 60-80°C under vacuum to obtain ferric ceria; (3) Disperse ferric ceria in ethanol, add organic copper salt, distilled water and ammonia water, wherein the molar ratio of ferric ceria to organic copper salt is 1:(0.04-0.1), and the volume ratio of ethanol, distilled water and ammonia water is 35-40:1:1. After ultrasonic treatment at room temperature for 15-30 min, heat in a water bath at 60-80 °C for 10-15 h. Separate the precipitate by centrifugation, wash with distilled water and ethanol for 3-5 times, and vacuum dry at 40-60 °C for 18-24 h to obtain a powder. Heat treat the dried powder at 400-500 °C under argon flow for 3-5 h to obtain a copper oxide-loaded ferric ceria material.

[0010] The present invention prepares the copper oxide loaded ferrocerate material by a chemical solution method. The copper oxide loading further improves the conductivity of the ferrocerate, which is further beneficial to improving the electrochemical performance of the material. The preparation process is relatively simple and easy to operate.

[0011] Preferably, in steps (1) and (2), the alcohol is one or a combination of methanol, ethanol or propanol.

[0012] Preferably, in step (1), the iron salt is one or a combination of ferric nitrate, ferric acetate or ferric citrate.

[0013] Preferably, in step (1), the cerium salt is one or a combination of cerium nitrate, cerium acetate or cerium sulfate.

[0014] Preferably, in step (1), the strong base is potassium hydroxide or sodium hydroxide or a combination thereof.

[0015] Preferably, in step (3), the organic copper salt is one or a combination of copper acetylacetonate or copper phenylacetate.

[0016] The present invention also provides a copper oxide-loaded cerium ferrite negative electrode material, which is prepared according to any of the above methods.

[0017] The invention provides application of a copper oxide-loaded cerium ferrite negative electrode material in a battery negative electrode material.

[0018] Beneficial effects: The present invention prepares a copper oxide loaded cerium ferrite negative electrode material by a chemical solution method. The conductivity of cerium ferrite is further improved by loading copper oxide, which is further beneficial to improving the electrochemical performance of the material. The preparation process provided by the present invention is relatively simple and easy to operate. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the cycle life diagram of copper oxide supported iron ceria in Example 1. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] Example 1 A copper oxide loaded iron ceria negative electrode material is prepared by a chemical solution method, and the preparation is carried out according to the following steps: (1) 100 mL of methanol / water was added into a flask at a volume ratio of 1:1, and then iron nitrate and cerium salt cerium nitrate were added into the methanol aqueous solution, wherein the molar stoichiometric ratio of iron to cerium was 1:1, and ultrasonic dispersion was performed for 10 min, and then 20 mL of 2M potassium hydroxide solution was added, and ultrasonic treatment was continued for 10 min to obtain a mixture; (2) After stirring the mixture at 60 °C for 8 h, the mixture was filtered and washed with 10 mL of methanol, and dried under vacuum at 60 °C overnight to obtain cerium ferrite; (3) Disperse ferric ceria in ethanol, add copper acetylacetonate, distilled water and ammonia water, wherein the molar ratio of ferric ceria to copper acetylacetonate is 1:0.04, and the volume ratio of ethanol, distilled water and ammonia is 35:1:1. After ultrasonic treatment at room temperature for 15 min, heat in a 60°C water bath for 15 h. Wash the precipitate obtained by centrifugation with distilled water and ethanol three times, and vacuum dry at 60°C for 18 h to obtain a powder. The dried powder is heat treated at 400°C under argon flow for 5 h to obtain a copper oxide-loaded ferric ceria material.

[0022] Figure 1This is the cycle life diagram of copper oxide loaded iron ceria. Under the current density of 500 mA / g, the first discharge capacity is 1770 mAh / g, the third discharge capacity is 889 mAh / g and the 50th discharge capacity is 825 mAh / g. Compared with the third discharge capacity, the capacity retention rate is 92.8%.

[0023] Example 2 A copper oxide-loaded iron ceria negative electrode material is similar to that in Example 1 and is prepared according to the following steps: (1) Add 100 mL of ethanol / water solution in a volume ratio of 1:1 into a flask, add ferric citrate and cerium sulfate into the ethanol-water solution, wherein the molar stoichiometric ratio of iron to cerium is 1:1, and perform ultrasonic dispersion for 20 min. Then, add 20 mL of 2 M strong base sodium hydroxide solution, and continue ultrasonic treatment to obtain a mixture; (2) After stirring the mixture at 80 °C for 5 h, the mixture was filtered and washed with 10 mL of alcohol, and dried under vacuum at 80 °C overnight to obtain cerium ferrite; (3) Disperse ferric ceria in ethanol, add copper styrene oxide, distilled water and ammonia water, wherein the molar ratio of ferric ceria to copper styrene oxide is 1:0.06, and the volume ratio of ethanol, distilled water and ammonia is 40:1:1. After ultrasonic treatment at room temperature for 30 min, heat in a water bath at 80 °C for 10 h. Wash the precipitate separated by centrifugation with distilled water and ethanol for 5 times, and vacuum dry at 60 °C for 24 h to obtain a powder. The dried powder is heat treated at 450 °C under argon flow for 4 h to obtain a copper oxide-loaded ferric ceria material.

[0024] Example 3 A copper oxide-loaded iron ceria negative electrode material is similar to that in Example 1 and is prepared according to the following steps: (1) Add 100 mL of propanol / water in a volume ratio of 1:1 into a flask, add acetate and cerium acetate into the propanol aqueous solution, wherein the molar stoichiometric ratio of iron to cerium is 1:1, and ultrasonically disperse for 10 min. Then, add 20 mL of 2 M strong base potassium hydroxide solution, and continue ultrasonic treatment for 10 min to obtain a mixture; (2) The mixture was stirred at 60 °C for 8 h, then filtered and washed with 10 mL of alcohol, and dried under vacuum at 60 °C overnight to obtain cerium ferrite; (3) Disperse ferric ceria in ethanol, add organic copper salt, distilled water and ammonia water, wherein the molar ratio of ferric ceria to organic copper salt is 1:00.1, and the volume ratio of ethanol, distilled water and ammonia is 38:1:1. After ultrasonic treatment at room temperature for 30 min, heat in a water bath at 80°C for 15 h. Wash the precipitate separated by centrifugation with distilled water and ethanol three times, and vacuum dry at 60°C for 20 h to obtain a powder. The dried powder is heat treated at 500°C under argon flow for 3 h to obtain a copper oxide-loaded ferric ceria material.

Claims

1. A method for preparing a copper oxide-loaded iron ceria negative electrode material, characterized in that: The method comprises the following steps: preparing a copper oxide-loaded iron ceria anode material by a chemical solution method; (1) Add 100 mL of alcohol / water solution in a volume ratio of 1:1 into a flask, add iron salt and cerium salt into the alcohol / water solution, where the molar ratio of iron to cerium is 1:1, and ultrasonically disperse for 10 to 20 min. Then add 20 mL of a 2 M strong base solution and continue ultrasonic treatment for 10 to 20 min to obtain a mixture; (2) After stirring the mixture at 60-80°C for 5-8 h, the mixture was filtered and washed with 10 mL of alcohol, and dried overnight at 60-80°C under vacuum to obtain ferric ceria; (3) Disperse ferric ceria in ethanol, add organic copper salt, distilled water and ammonia water, wherein the molar ratio of ferric ceria to organic copper salt is 1:(0.04-0.1), and the volume ratio of ethanol, distilled water and ammonia water is 35-40:1:

1. After ultrasonic treatment at room temperature for 15-30 min, heat in a water bath at 60-80 °C for 10-15 h. Separate the precipitate by centrifugation, wash with distilled water and ethanol for 3-5 times, and vacuum dry at 40-60 °C for 18-24 h to obtain a powder. Heat treat the dried powder at 400-500 °C under argon flow for 3-5 h to obtain a copper oxide-loaded ferric ceria material.

2. The method for preparing a copper oxide-loaded iron ceria negative electrode material according to claim 1, characterized in that: The alcohol is one of methanol, ethanol or propanol or a combination thereof.

3. The method for preparing a copper oxide-loaded iron ceria negative electrode material according to claim 1, characterized in that: In step (1), the iron salt is one of ferric nitrate, ferric acetate or ferric citrate or a combination thereof; the cerium salt is one of cerium nitrate, cerium acetate or cerium sulfate or a combination thereof.

4. The method for preparing a copper oxide-loaded iron ceria negative electrode material according to claim 1, characterized in that: In step (1), the strong base is potassium hydroxide or sodium hydroxide or a combination thereof.

5. The method for preparing a copper oxide-loaded iron ceria negative electrode material according to claim 1, characterized in that: In step (3), the organic copper salt is copper acetylacetonate or copper phenylacetate, or a combination thereof.

6. The method for preparing a copper oxide-loaded iron ceria negative electrode material according to any one of claims 1 to 5, characterized in that: Prepare as follows: (1) 100 mL of methanol / water was added into a flask at a volume ratio of 1:1, and then iron nitrate and cerium salt cerium nitrate were added into the methanol aqueous solution, wherein the molar stoichiometric ratio of iron to cerium was 1:1, and ultrasonic dispersion was performed for 10 min, and then 20 mL of 2 M potassium hydroxide solution was added, and ultrasonic treatment was continued for 10 min to obtain a mixture; (2) After stirring the mixture at 60 °C for 8 h, the mixture was filtered and washed with 10 mL of methanol, and dried under vacuum at 60 °C overnight to obtain cerium ferrite; (3) Disperse ferric ceria in ethanol, add copper acetylacetonate, distilled water and ammonia water, wherein the molar ratio of ferric ceria to copper acetylacetonate is 1:0.04, and the volume ratio of ethanol, distilled water and ammonia is 35:1:

1. After ultrasonic treatment at room temperature for 15 min, heat in a 60°C water bath for 15 h. Wash the precipitate obtained by centrifugation with distilled water and ethanol three times, and vacuum dry at 60°C for 18 h to obtain a powder. The dried powder is heat treated at 400°C under argon flow for 5 h to obtain a copper oxide-loaded ferric ceria material.

7. The method for preparing a copper oxide-loaded iron ceria negative electrode material according to any one of claims 1 to 5, characterized in that: Prepare as follows: (1) 100 mL of ethanol / water solution was added into a flask at a volume ratio of 1:1, and ferric citrate and cerium sulfate were added into the ethanol / water solution, wherein the molar stoichiometric ratio of iron to cerium was 1:1, and ultrasonic dispersion was performed for 20 min. Then, 20 mL of 2 M strong base sodium hydroxide solution was added, and ultrasonic treatment was continued to obtain a mixture; (2) After stirring the mixture at 80 °C for 5 h, the mixture was filtered and washed with 10 mL of alcohol, and dried under vacuum at 80 °C overnight to obtain cerium ferrite; (3) Disperse ferric ceria in ethanol, add copper styrene oxide, distilled water and ammonia water, wherein the molar ratio of ferric ceria to copper styrene oxide is 1:0.06, and the volume ratio of ethanol, distilled water and ammonia is 40:1:

1. After ultrasonic treatment at room temperature for 30 min, heat in a water bath at 80 °C for 10 h. Wash the precipitate separated by centrifugation with distilled water and ethanol for 5 times, and vacuum dry at 60 °C for 24 h to obtain a powder. The dried powder is heat treated at 450 °C under argon flow for 4 h to obtain a copper oxide-loaded ferric ceria material.

8. The method for preparing a copper oxide-loaded iron ceria negative electrode material according to any one of claims 1 to 5, characterized in that: Prepare as follows: (1) Add 100 mL of propanol / water in a volume ratio of 1:1 into a flask, add acetate and cerium acetate into the propanol aqueous solution, wherein the molar stoichiometric ratio of iron to cerium is 1:1, and ultrasonically disperse for 10 min. Then, add 20 mL of 2 M strong base potassium hydroxide solution, and continue ultrasonic treatment for 10 min to obtain a mixture; (2) The mixture was stirred at 60 °C for 8 h, then filtered and washed with 10 mL of alcohol, and dried under vacuum at 60 °C overnight to obtain cerium ferrite; (3) Disperse ferric ceria in ethanol, add organic copper salt, distilled water and ammonia water, wherein the molar ratio of ferric ceria to organic copper salt is 1:00.1, and the volume ratio of ethanol, distilled water and ammonia is 38:1:

1. After ultrasonic treatment at room temperature for 30 min, heat in a water bath at 80°C for 15 h. Wash the precipitate separated by centrifugation with distilled water and ethanol three times, and vacuum dry at 60°C for 20 h to obtain a powder. The dried powder is heat treated at 500°C under argon flow for 3 h to obtain a copper oxide-loaded ferric ceria material.

9. A copper oxide-loaded cerium ferrite negative electrode material, characterized in that Prepared according to any one of claims 1 to 8.

10. Use of the copper oxide loaded cerium ferrite according to claim 9 in a lithium battery negative electrode material.